THE GAMHER RESEARCH PROJECT FOR METRIC DOCUMENTATION OF CULTURAL HERITAGE: CURRENT DEVELOPMENTS - G. Bitelli (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2019)
GAMHer (Geomatics data Acquisition and Management for landscape and built Heritage in a European perspective) is a three-year research project financed under the Italian PRIN 2015 framework (Progetti di Ricerca di Rilevante Interesse Nazionale). The project, started in February 2017 under the University of Bologna coordination, links other 5 Italian research groups mainly involved in Cultural Heritage (CH) documentation and data management: Politecnico di Milano, Politecnico di Torino, IUAV Venice, University of Florence, University of Cassino and Southern Lazio and University of Bergamo. GAMHer aims at exploiting some research and practical challenges in those disciplines devoted to generate 3D models for objects related to both landscape and built heritage; primary focus is then on digital photogrammetry and 3D scanning. These techniques are more and more applied in different contexts, having as the main subjects monuments, buildings, natural and urban landscapes. Some critical points however remain for their implementation, also facing to the new European directives, strictly connected to the requirement of the Digital Agenda for Europe. A wider use of digital data has to be achieved, in Europe as well as internationally, and therefore an analysis of the current developments is significant, together with a critical assessment of their performances.